Pengaruh CAR, NIM, dan BOPO terhadap ROA pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2024 - Pratama, Muhammad Aliff; Susanto, Heri; Pranamulia, Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study analyzes the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Operational Efficiency Ratio (BOPO) on Return on Assets (ROA) in 36 banks listed on the Indonesia Stock Exchange (IDX) in 2024. The analysis was conducted using multiple linear regression, including a simple robustness test through winsorizing to reduce the influence of outliers. The results show that BOPO has a significant negative effect on ROA in both the original model (β = –0.086; p < 0.001) and winsorized data (β = –0.090; p = 0.000), while NIM has a significant positive effect in the original model (β = 0.096; p = 0.031) but is not significant after winsorizing (β = 0.075; p = 0.070), and CAR has no significant effect in both models. Simultaneously, all three independent variables influenced ROA (F = 87.036; p < 0.001). The regression model explained 89.1% of the variation in ROA in the initial model and 91.0% after winsorizing, confirming the stability of the results. These findings emphasize that bank profitability is significantly influenced by operational efficiency and net interest margin management, while capital adequacy does not contribute significantly. Robustness tests confirmed the validity of the model, showing that conclusions remained consistent even when the data was smoothed to remove outliers.